11 The European Dimension of Education - axiological component of the European educational policies - Corina GHEORGHIU (Association of Social and Educational Innovation, 2016)
The axiological dimension of the curriculum supposes on the one hand the spreading of some specific internal values and on the other hand the potentiality of connecting and giving a meaning to the external values, to the totally different cultural and social stimuli.